Bridging neurology and psychiatry: establishing Latin America’s first dedicated Neuropsychiatry Ward at IPq-HCFMUSP - Lacerda, Daniele Costa Rachid; Sousa, Lucas D’Andrea Pereira; Obeid, Maruan; Santos, Livia Souza; Bozutti, Luis Antonio; Marchetti, Renato Luiz (Frontiers in Psychiatry, 2025)
BackgroundThe convergence of neurology and psychiatry has become critical for managing disorders with overlapping neurological and psychiatric features. To fill a service gap in Latin America, Brazil’s first Neuropsychiatry Ward (ENPQ) opened at the Institute of Psychiatry, Hospital das Clínicas, University of São Paulo in December 2024. This study describes the ward’s rationale, structure, and early clinical outcomes.MethodsWe performed a retrospective descriptive analysis of all 26 adult admissions to the ten-bed ENPQ from 1 December 2024 to 11 April 2025. We extracted age, sex, length of stay (LOS), primary diagnosis, and 30-day readmission from electronic records and computed descriptive statistics.ResultsPatients had a mean age of 48.0 ± 15.4 years (69.2% female), with one-third aged ≥ 60 years. Epilepsy was the most common primary diagnosis (46.2%), followed by Bipolar affective disorder, Depressive disorder and Schizophrenia (7.7% each). The mean LOS was 26.1 days, and only two patients (7.6%) were readmitted within 30 days—a rate lower than those reported for both general psychiatric wards (≈16%) and tertiary neurology wards (≈12.5%).ConclusionsIn this study, an integrated neuropsychiatry ward demonstrated feasibility in a public quaternary hospital and yielded a lower 30-day readmission rate than non-integrated settings, despite a complex referral population and a LOS comparable to standard care. These findings support further prospective, controlled studies to confirm the benefits of integrated neurologic and psychiatric management.